Estilo de vida y adherencia terapéutica en personas diagnosticadas con diabetes mellitus tipo 2 que residen en el barrio Obrapia, Loja - Maza Guamán, Lady Johanna (2024)
Lifestyle and therapeutic adherence are behaviors that each individual develops and, when applied correctly, help people with type 2 diabetes mellitus prevent complications, resulting in well-being throughout their life. This research aimed to describe the lifestyle, identify therapeutic adherence according to age and sex, and establish the relationship between lifestyle and therapeutic adherence in people diagnosed with type 2 diabetes mellitus who reside in the Obrapia neighborhood, in Loja. The study used a quantitative cross-sectional cohort approach, with a sample of 59 participants. They were given informed consent and the IMEVID (Lifestyle Measurement Questionnaire) and MBG (Martin Bayarre Grau) questionnaires to assess treatment adherence. The results showed that 38.98% (n=23) had a good lifestyle and 61.02% (n=36) had an inadequate lifestyle, with a predominance of females between the ages of 41 and 64. Regarding therapeutic adherence, 57.62% (n=34) had good adherence to treatment, while 42.37% (n=25) had partial adherence, and no people with poor therapeutic adherence were found. In terms of age and sex group distribution, the female sex of mature adults prevailed. When relating the variables, a p-value of 0.00002861 was obtained, which demonstrated that there is a statistically significant relationship. It is concluded that lifestyle influences therapeutic adherence in people with type 2 diabetes mellitus